Analisis Sistem Informasi Akuntansi dalam Menunjang Kualitas Laporan Keuangan pada KSP Kopdit Tuke Jung Kantor Pusat Nelle - Weking, Rofina Beto; Herdi, Henrikus; Rengga, Andreas (BUDGETING : Journal of Business, Management and Accounting, 2024)
This study aims to determine and analyze the application of accounting information systems in supporting the quality of financial statements at KSP Kopdit Tuke Jung Nelle Head Office. The data collection used in this study used observation, interview, and documentation methods. This type of research uses qualitative descriptive. Using this qualitative descriptive method, researchers describe and describe and analyze the application of accounting information systems in supporting the quality of financial statements at KSP Kopdit Tuke Jung Nelle Head Office. The results of this study show that the application of the accounting information system at the KSP Kopdit Tuke Jung Nelle Head Office has been implemented but there is still a lack of relevance in presenting quality financial statements because there are still delays in the submission of financial statements. Keywords : Accounting Information Systems, Quality of Financial Reports.